Analisis Sistem Pengendalian Internal Menunjang Akuntabilitas Dalam Meminimalisir Kecurangan - Rachyu Purbowati; Nurhayati Nurhayati (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2020)
The purpose of this study is to Know the Implementation of Internal Control Systems in Supporting Accountability in Minimizing Cheating at KPRI-Bahagia. This research is a descriptive qualitative study. The method of data collection is done using the method of observation, interviews and documentation. The data analysis technique is done through four stages, namely through data collection, data reduction, data presentation and conclusion drawing. The results showed that the internal control system was able to support accountability in minimizing fraud, both with steps to improve and develop the KPRI-Bahagia internal control system.